Hubungan Komorbid dengan Mortalitas dan Lama Rawat Inap pada Pasien COVID-19 di Rumah Sakit UNS Surakarta - Gregorius Prama Suryaputra; Hendrastutik Apriningsih; Meirina Mulia Wardani (Fakultas Kedokteran, Universitas Sebelas Maret, 2022)
Background: Comorbid COVID-19 patients have worse outcomes or even death and have a longer length of stay than patients without comorbidities. The purpose of the study was to determine the relationship between comorbidities and mortality rates in COVID-19 patients at the UNS Surakarta Hospital. Methods: An analytical observational study with a cross sectional approach, conducted in January-June 2021 at UNS Sukoharjo Hospital. The subjects of this study were patients, COVID-19 who were treated at UNS Sukoharjo Hospital. Sampling was carried out by purposive sampling and obtained a sample of 132 people consisting of 66 COVID-19 patients with comorbidities and 66 COVID-19 patients without comorbidities. Data collection using medical records was then analyzed statistically using the bivariate test with Chi Square (χ²) and Mann-Whitney test. Results: Out of 132 samples, 26 samples have mortality as the outcome, with 20 patients having comorbid and 6 patients having no comorbid. Diabetes mellitus is the most frequent comorbid. To identify the effect of comorbid on mortality, chi-square test showed that the value is P=0.002. The mean value of Length of Stay in patients with comorbid is 10.18±5.94 days and without comorbid is 10.47±4.72 days. The results of the Mann Whitney test analysis obtained P value= 0.510. Conclusion: There is a significant relationship between comorbidities and mortality rates and there is no relationship between comorbidities and length of stay in COVID-19 patients at UNS Hospital Surakarta. Keywords: comorbidity, mortality rate, length of hospitalization.